Influenza Vaccines for the Future - Rappuoli, Rino.; Rappuoli, Rino.; Del Giudice, Giuseppe.; Del Giudice, Giuseppe. (Birkhäuser Advances in Infectious Diseases,, 2011)
The emergence of H5N1 avian influenza in 1997 and of the influenza A H1N1 of swine origin in 2009 calls for new, rapid and sustainable solutions for both seasonal and pandemic influenza viruses. During the last ten years, science and technology have made enormous progress, and we are now able to monitor in real time the genetics of viruses while they spread globally, to make more powerful vaccines using novel adjuvants, and to generate viruses in the laboratory using reverse genetics. This volume not only provides state-of-the-art information on the biology of influenza viruses and on influenza vaccines, but is also designed to be a resource to face the present H1N1 pandemic and to plan for long-term global and sustainable solutions.